Teacher Professionalism in Primary Education: An Integrative Framework of Relational Practice, Professional Development, and Instructional Leadership - Ilmi Amalia Maghfiroh; Nur Mahmudah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Teacher professionalism is increasingly recognized as a multidimensional construct that extends beyond pedagogical competence to encompass relational, moral, and contextual dimensions of teaching, particularly in primary education. This study examines how teacher professionalism is enacted through the interaction of relational–moral practices, continuous professional development, instructional leadership, parental engagement, and professional resilience under infrastructural constraints. Adopting a qualitative case study design, data were collected through semi-structured interviews with 12 informants (eleven classroom teachers and one school leader), complemented by observations and document analysis. The data were analyzed inductively using thematic analysis. The findings reveal that teacher professionalism is shaped by emotionally supportive and parental-like practices, sustained engagement in professional learning, collaborative and supportive instructional leadership, active teacher–parent communication, and adaptive responses to limited school infrastructure. These dimensions operate in an interconnected manner rather than as isolated professional attributes. This study contributes to the literature by proposing an integrative and context-sensitive conceptual framework that reconceptualizes teacher professionalism as a relationally grounded, morally informed, and institutionally embedded practice. The framework offers an analytical lens for future research and provides practical insights for strengthening teacher professionalism in primary education contexts characterized by strong community involvement and structural constraints.